«Uncreated Wisdom» and «Participated Wisdom» according to Meister Eckhart - Bara Bancel, Silvia (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2022)
We propose here a first study of the notion of wisdom according to Meister Eckhart, based on his Latin writings, notably his Commentary on the Book of Wisdom (In Sap. n.121, 201‑206, 243 and 272‑274), the Sermons and Lessons on Ecclesiasticus (In Eccli.), and the Latin Sermons: Sermo die b. Augustini Parisius habitus and Sermo LV, as well as the German Sermons 95a, 95b and 112. God, his nature, and the Son are referred to by Eckhart as divine wisdom (sapientia increata), which is also the source of all human wisdom (sapientia participata). Beyond earthly or natural wisdom, there is another wisdom that comes from the presence of God, “a kind of tasty knowledge”, the foretaste of the divine sweetness, which is none other than the birth of God, beyond the human faculties, in the ground of the soul.